Predictors of the Perception of Smoking Health Risks in Smokers With or Without Schizophrenia - Kowalczyk, William J. (J Dual Diagn, 2016)
OBJECTIVE: This study sought to examine the predictors of health risk perception in smokers with or without schizophrenia. METHODS: The health risk subscale from the Smoking Consequences Questionnaire was dichotomized and used to measure health risk perception in smokers with (n = 67) and without schizophrenia (n = 100). A backward stepwise logistic regression was conducted using variables associated at the bivariate level to determine multivariate predictors. RESULTS: Overall, 62.5% of smokers without schizophrenia and 40.3% of smokers with schizophrenia completely recognize the health risks of smoking (p ≤ .01). Multivariate predictors for smokers without schizophrenia included: sex (Exp (B) = .3; p < .05), Smoking Consequences Questionnaire state enhancement (Exp (B) = .69; p < .01), and craving relief (Exp (B) = 1.8; p < .01). Among smokers with schizophrenia, predictors were education (Exp (B) = .7; p < .05), nicotine dependence (Exp (B) = .5; p < .01), motivation to quit (Exp (B) = 1.8; p < .01), and Smoking Consequences Questionnaire craving relief (Exp (B) = 1.8; p < .01). CONCLUSIONS: There was overlap and differences between predictors in smokers with and without schizophrenia. Commonly used techniques for education on the health consequences of cigarettes may work in smokers with schizophrenia, but intervention efforts specifically tailored to smokers with schizophrenia might be more efficacious.